2020
DOI: 10.1101/2020.10.09.332965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific maturational trajectory of endocannabinoid plasticity in the rat prefrontal cortex

Abstract: The prefrontal cortex (PFC) develops until early adulthood in rodents and humans, but how synaptic plasticity evolves throughout postnatal development is not known. Here, we used a cross-sectional approach to establish the postnatal maturational trajectories of intrinsic properties and synaptic plasticity in the PFC of rats of both sexes. We found that while layer 5 PFC pyramidal neurons from rats of both sexes displayed similar current-voltage relationships, rheobases and resting potentials across all age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In line with this hypothesis, the number of action potentials in response to depolarizing steps is lower in adult females than pubescent or juvenile females, an effect of age that is not seen in males [ 53 ]. This recapitulates previously published data demonstrating prepubescent females have enhanced excitability in medium spiny neurons within the striatum compared to males [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this hypothesis, the number of action potentials in response to depolarizing steps is lower in adult females than pubescent or juvenile females, an effect of age that is not seen in males [ 53 ]. This recapitulates previously published data demonstrating prepubescent females have enhanced excitability in medium spiny neurons within the striatum compared to males [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are reported aspects of transmission in this region that do not differ between males and females. Maturational trajectories of current–voltage curves, resting membrane potentials, rheobases, mGluR2/3-mediated LTD, and paired pulse ratios in layer V of the PFC are similar between the sexes in rats [ 53 ]. Additionally, field excitatory postsynaptic potentials are similar between the sexes across multiple age groups [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the input profile and the release probability of excitatory synapses to prefrontal cortex (PFC) pyramidal neurons were consistent between pubescence and adulthood in both sexes ( Bernabeu et al., 2020 ). In the BLA, the input-output curves built in pubescent rats reached higher maxima than in adults, in support of the idea that the BLA reaches maturity late in life.…”
Section: Discussionmentioning
confidence: 99%
“…The ECS plays a specific role in neural development by controlling the establishment of cortical-subcortical connections [ 46 ]. In this regard, a study by Bernabeu et al (2020) analyzed the postnatal maturation trajectories of layer 5 pyramidal PFC synapses at different postnatal stages [ 53 ]. They found that endocannabinoid-mediated long-term depression (LTD) was sexually dimorphic, even though CB1s were functional in both sexes during all developmental stages.…”
Section: The Endocannabinoid System (Ecs)mentioning
confidence: 99%